Cross-disciplinary investigation of gas seepage at Storbanken high and the Olga basin, The northern Barents Sea - Amdal, Frank Andreas (UiT Norges arktiske universitet, 2019)
The eastern parts of the northern Barents Sea is a little explored sector of the Barents Sea which currently is not open for petroleum activity. This thesis focuses on the processes and mechanisms controlling gas seepage activity in the Olga basin and Storbanken high. 2D seismic and bathymetric data has been correlated with water column acoustic data to identify gas bubbles in the water column and active seeping sites. A simplified maturation modeling of source rocks suggested that the Botneheia Formation and Billefjorden Group is gas generating. Gas is believed to migrate vertically from these formations through leaking faults (F1, F2, F4, F6 and FZ) and gas chimneys (GC1-GC3 and GCZ). Direct migration from the Botneheia Formation source rock to the reservoir of De Geerdalen/Snadd Formation is also possible in the gas mature areas of the Olga basin and potentially in the deeper parts of the Storbanken high. Post-Early Cretaceous extension, most likely related to the uplift of Storbanken high, is believed to developed NW-SE striking normal faults (FZ). The normal fault zone (FZ) is regarded as a vital migration pathway potentially transporting gas from the Botneheia Formation source rock and distributing gas from the reservoir of the De Geerdalen/Snadd Formation to the Realgrunnen Subgroup. NE-SW striking reverse faults (F5) at the Kong Karls Land platform has suggested compression in Early Cretaceous, an important tectonic event tilting the stratigraphy towards the northwest favoring lateral migration towards the Storbanken high. Gas flares identified above outcropping formations has indicated lateral migration along the cap rocks of the Flatsalen Formation and Agardhfjellet Formation. Pockmarks were mainly restricted to the intersection of the Olga basin and Storbanken high. The distinct distribution is believed to be governed by the glacigenic sediments which accumulated within a glacial trough carved by the lithologically controlled erosion of the Agardhfjellet Formation. The pockmarks, craters and craters ...